Institutions and Firm’s Participation in the Global Production Network (GPN): Firm-Level Analysis in Indonesia - Eneng Herlin Herlina; Toshihiro Kudo (Jurnal Ekonomi dan Studi Pembangunan, 2020)
This paper argues that besides firm’s internal factors, institutions may also affect a firm’s participation in the production network. By analyzing the effect of access to credit, import license, and competition from the informal sector, this study attempts to provide an empirical study about institutions and firms’ participation in the Global Production Network (GPN), study case in Indonesia. A logistic regression analysis shows that most variables are statistically significant, with some variations between larger firms and Small Medium Enterprises (SMEs). Access to credit, as an obstacle, negatively influences SMEs’ participation, implying that SMEs in Indonesia are still constrained by financial institutions. Meanwhile, an import license can be regarded as the most crucial factor for the larger companies and SMEs, implying that it provides firms with more access to resources that may benefit their competitiveness. On the other hand, the informal sector tends to more negatively affect the larger firms than the SMEs, suggesting that its impact occurs through a specific channel. The findings highlight the influence of institutions on a firm’s participation in the GPN and provide certain policy implications, i.e., financial development systems, signaling policies, simplifying procedures of granting import permits, and implementing a tax for the informal firms.